(E)-3-(4-Hexyloxyphenyl)-1-(3-hydroxyphenyl)prop-2-en-one - Zainab, Ngaini; Siti Muhaini, Haris Fadzillah; Norashikin Irdawaty, bdul Rahman; Hasnain, Hussain; Ibrahim, Abdul Razak; Fun, Hoong-Kun (International Union of Crystallography, 2009)
In the title compound, C21H24O3, the enone unit is in the s–cis configuration. The dihedral angle between the benzene rings is 2.18 (4). In the crystal, molecules are linked by pairs of O— HO intermolecular hydrogen bonds, forming inversion dimers. The crystal structure is also consolidated by C—H interactions.